Transit-oriented development for older people: Does using multiple public transport options improve their physical and mental health? - Yao Du; Guibo Sun; Mei-po Kwan (Journal of Transport and Land Use)
Transit-oriented cities often use urban rail transit (e.g., metro) to lead public transport development (TOD), which might overlook other public transport options (e.g., bus) that matter for the health and wellbeing of older people. We investigate older people’s public transport use patterns and how multiple public transport options are related to the physical and mental health of older people.